The Influence of Consumer Perceptions, Price and Product Quality on Purchasing Decisions for Tawas Natural Spray Deodorant - Fitriyah, Rohmatul; Widiana, Muslichah Erma; Kharismawati, Ika (Universitas Bhayangkara Surabaya, 2025)
This study aims to analyze how consumer perceptions, price, and product quality influence purchasing decisions for alum natural spray deodorants, especially for students at the Faculty of Economics and Business, Bhayangkara University Surabaya. A total of 84 respondents were sampled in this study, which were selected through purposive sampling technique with the application of the Slovin formula. Data collected through questionnaires filled by respondents using a Likert scale, and supported by literature data. The analysis methods used in this study include research instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results showed that consumer perceptions, price, and product quality have an influence both partially and simultaneously on purchasing decisions for alum natural spray deodorants for students of the Faculty of Economics and Business, Bhayangkara University Surabaya.